INDIA (Fiep Bulletin - online, 2015)
It was in the colourfull Bosphorus that J. G. happened to travel with G. L. Delegates to the Third world congress were on a pleasure trip over the bosphorus at Istanbil when Mr. Thulin drew near me deeply thinking over the Programme of demonstration by the Indian Gymnasts witnessed on the previous night.